Electro-fenton degradation of simulated petroleum wastewater by using Fe78Si9B13 metallic glasses - Xiao-Chen Xu; Zhong-Ling Shi; Ke-Qiang Qiu (Materials Research Express, 2020)
As the standard for the effluent from petroleum wastewater (PW) treatment become more and more strict, we adopt electro-Fenton (EF) oxidation method to degrade the simulated PW to surpass the limitations of conventional methods. The effects of initial pH value, current density, initial oil & grease (O&G) and initial chemical oxygen demand (COD) concentration on the degradation efficiency of the simulated PW were investigated on the premise of putting Fe _78 Si _9 B _13 glassy ribbon as the anode and graphite plate as the cathode, respectively. The results show that under the optimal parameters, the COD and O&G removal rates can reach up to 89.6% and 93.8%, respectively. Compared to the traditional Fenton method, the EF method we used shows the advantages of reducing H _2 O _2 consumption, power consumption, electrode mass loss and electrolysis time.